Expenditure behavior and children's welfare: an analysis of female headed households in Jamaica - Handa, Sudhanshu (Elsevier, 1996)
Evidence from Jamaica shows that the sex and union status of the household head can have a significant influence on household expenditure behavior with implications for individual household members. While the presence of a female decision maker generally increases the share of the household budget allocated to child and family goods, female headed households (FHHs) also spend more on adult wear and less on health. Lower health expenditures are partially offset by the differential use of other health inputs in FHHs. These differences in resource allocation may explain why poorer FHHs do not necessarily have lower children's outcomes in developing countries.